Communities' belief and attitude towards upgrading Marang as Tourism Hub in Terengganu - Mohd Huzairil Nizam Ibrahim
Tourism industry is important for economic development of many countries inclusive Malaysia. Malaysian tourists travelling to local destinations and abroad to foreign countries; and vice versa Malaysia receives millions of tourists who travels around the globe for relaxation with families or friends, attending events, working, and even for medical treatments. Marang district in Terengganu, Malaysia is well known for its beautiful islands, craft and traditional activities that attracts both local and foreign tourist for many years; and there is high potential for Marang to be upgrade to tourism hub for Terengganu state. Therefore, the objective of this research is to firstly, determine ifits communities has the belief that tourism hub will benefits from the positive impacts of tourism inclusive the economic development, higher standards of living, communication and integration of the societies, cultural exposure to tourist, infrastructure development and many others. Secondly, this research will explore the communities' attitude if Marang district is to be upgrade as the tourism hub. Thirdly, the relationship between the communities' belief and attitude is analysed. Lastly, investigation is also conducted to determine if there are any variances in belief and attitude for four communities' groups of local communities, communities' leaders, business owners, local government and authorities. The theoretical framework of this research is based on the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB). The research design is quantitative whereby survey using questionnaires was distributed in the Marang district; and able to collect feedback from 414 respondents. Cluster and simple random sampling are used to gather information from four different groups of communities. The findings show that the communities' belief is high, and their attitude is positive. Using Spearman Coefficient Correlation, it was found that there is a significant positive relationship between communities' belief and attitude; but the relationship is not strong. One Way ANOVA reveals that there are no differences in belief between the four groups; but their attitude has variances between each other. This research contributes on better understanding of the local communities' behavioural aspects for government to make better decisions in development of the tourism industry. This research can further extend to get feedback from local and foreign tourists and can also be conducted in other parts of tourist destination in Terengganu or for the whole Malaysia in becoming tourism hub in near future.